A Structural-Functional Approach to the Sacrifice Ritual in Alevism - Köse, Serkan (Journal of Alevism-Bektashism Studies, 2017)
Alevi belief forms its legitimate basis with the existence of “ocak” and “dede” institutions. While “cem” rituals create the basic act mechanism of Alevi belief, sacrifice occurs as the communication system of the rituals in question. Sacrifice, both bloody and bloodless, takes centre place in “cem” rituals. The basic hypothesis of this paper is that in Alevism the sacrifice rituals are central ritual practice within ritual. The paper intends to make an analysis in this direction based on the data acquired from both field and literature search. It is used a structural-functional approach which explains the existence of structure with the existence of functional mechanism, and asserts that a dysfunctional structure will possible disappear. Therefore, on the one hand, it will be provided an analysis by using different approaches to the sacrifice rituals in Alevism, and on the other hand, it will be seen the position of the sacrifice rituals within the belief in question. With reference to these ideas, the paper pursues two-way goal: first, functional position of the sacrifice ritual in the context of Alevi belief and its influence on the structure; and second, change/transformation of the sacrifice rituals performed within the old Turkish belief and Alevism.
Keywords: Alevi; sacrifice ritual; old Turkish beliefs; folklore; structural-functional theory